Perbandingan strategi Koperasi Pegawai Republik Indonesia - Sholahudin, Aris Athoillah (Maliki Interdisciplinary Journal, 2024)
Strategy explains how a company tries to achieve its goals. The strategy must be in accordance with the company's goals, vision and mission. This research took the subject of the Republic of Indonesia Employee Cooperative "Bina Raharja" and the Republic of Indonesia Employee Cooperative "Bhakti Praja" as samples. The aim of this research is to compare and identify differences in strategies between the two cooperatives. This research use case study and the data used is secondary data. This analysis shows that the approach used by each cooperative is different and unique according to their goals, which allows them to survive and continue to improve their quality both in terms of human resources and in developing the cooperative business itself which can demonstrate its respective advantages and qualities.